2013
DOI: 10.1063/1.4821239
|View full text |Cite
|
Sign up to set email alerts
|

Development of microcracks in hydrogen-implanted silicon substrates

Abstract: The development of microcracks in hydrogen-implanted silicon has been studied up to the final split using optical microscopy and mass spectroscopy. It is shown that the amount of gas released when splitting the material is proportional to the surface area of microcracks. This observation is interpreted as a signature of a vertical collection of the available gas. The development of microcracks is modeled taking into account both diffusion and mechanical crack propagation. The model reproduces many experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…8,21,22 The cavities buried in the implanted region of the samples were imaged by optical microscopy. 23 Finally, the blisters eventually appearing on the wafer surface were characterized by atomic force microscopy (AFM). 24,25 Figure 1 shows the H and He depth profiles measured by SIMS in the co-implanted samples (H first, Fig.…”
Section: Experimental Details and Methodologymentioning
confidence: 99%
“…8,21,22 The cavities buried in the implanted region of the samples were imaged by optical microscopy. 23 Finally, the blisters eventually appearing on the wafer surface were characterized by atomic force microscopy (AFM). 24,25 Figure 1 shows the H and He depth profiles measured by SIMS in the co-implanted samples (H first, Fig.…”
Section: Experimental Details and Methodologymentioning
confidence: 99%
“…Implant / cleave wafers. Optical microscopy with heating a stage and mass spectroscopy are useful in characterizing hydrogen-implanted silicon used in the implant/cleave wafering scheme, and it was found that the amount of gas released when splitting the material is proportional to the surface area of microcracks [169]. Transmission electron microscopy has also been used in connection to the implant/cleave wafering scheme [170].…”
Section: Metrology Techniques For New Wafering Methodologies and Subsmentioning
confidence: 99%
“…1.27) as the microcracks have a typical diameter of several micrometers. 92 Several scenarios have been put forward for microcrack development. It has been proposed that cracks interact in the same way as platelets do and that the exchange of gas between differently sized cracks is the driver for their evolution.…”
Section: Microcrack Developmentmentioning
confidence: 99%